2015
DOI: 10.1016/j.leukres.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

High MN1 expression increases the in vitro clonogenic activity of primary mouse B-cells

Abstract: The MN1 (Meningioma 1) gene is overexpressed in certain subtypes of acute myeloid leukemia (AML) and high levels of MN1 expression in mouse bone marrow cells results in myeloid leukemia. We showed that compared with control bone marrow (BM) MN1 expression was increased (2-fold or more) in 29 out of 73 (40%) pediatric B-cell acute lymphoblastic leukemia (B-ALL) patient BM. Additional analysis of MN1 expression in sub-groups within our cohort carrying different chromosome translocations showed that carriers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Kandilci A. et al reported that CEBPA downregulation contributes to MN1modulated leukemogenesis, and reintroduction of CEBPA in MN1-overexpressing hematopoietic cells prevents their hyperproliferation and restores myeloid differentiation [19]. Besides, MN1 has been reported significantly upregulated in ETV6-AML1-positive B-cell acute lymphoblastic patients [20]. MN1 has also been observed to fuse with another ETS family of transcription factors gene FLI1 in acute megakaryoblastic leukemia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Kandilci A. et al reported that CEBPA downregulation contributes to MN1modulated leukemogenesis, and reintroduction of CEBPA in MN1-overexpressing hematopoietic cells prevents their hyperproliferation and restores myeloid differentiation [19]. Besides, MN1 has been reported significantly upregulated in ETV6-AML1-positive B-cell acute lymphoblastic patients [20]. MN1 has also been observed to fuse with another ETS family of transcription factors gene FLI1 in acute megakaryoblastic leukemia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis suggests that the peripheral blood CD19 + B cells pool in JIA-U− and JIA-U+ patients display an overall remarkably similar transcriptome, also compared to controls. The differential expression analysis revealed only six differently expressed genes (DEGs) after FDR correction, which suggests that these differences are unlikely robust, but included genes such as TXNIP – related to B cell associated germinal centers in peripheral lymphoid organs ( 31 ) and MN1 , linked to colony forming activity of B cells ( 32 ). Polymorphisms (SNPs) in the HLA-DPB1 gene are associated with the susceptibility to uveitis in JIA ( 7 ), but the gene expression of HLA-DPB1 was (slightly) decreased in JIA cases either with or without uveitis compared to controls (JIA-U+, Log2[FC] = −0.33, P = 0.016; JIA-U−, Log2[FC] = −0.34, P = 0.013).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, its potential relationship with leukemia, including AML, has also been described [14]. It is reported that high expression of MN1 was shown to be a predictor of poor clinical outcome in AML patients with a normal karyotype [15] and ectopic expression of MN1 in mouse bone marrow cells led to myeloid leukemia [16, 17]. Moreover, MN1 overexpression in mouse and human hematopoietic stem/progenitor cells resulted in the abnormal proliferation and arrest of myeloid differentiation [18], while suppression of MN1 in leukemia cells inhibited their proliferation [19].…”
Section: Introductionmentioning
confidence: 99%